Transforming growth factor β (TGF-β) levels in the conditioned media of human bone cells: relationship to donor age, bone volume, and concentration of TGF-β in human bone matrix in vivo - Bismar, Hanadi; Klöppinger, T; Schuster, Elke Maria; Balbach, S; Diel, Ingo J.; Ziegler, Reinhard; Pfeilschifter, Johannes (Bone, 1999)
Transforming growth factor-β (TGF-β) is thought to play an important role in human bone remodeling. In the present study, we examined constitutive differences in TGF-β levels in primary bone cell cultures from the iliac crest of 112 women, aged 28-79 years. TGF-β1 was the major TGF-β isoform in the conditioned media, as determined by neutralizing TGF-β activity with specific antibodies against TGF-β1-3 in the mink lung cell bioassay, and by enzyme-linked immunoassay (ELISA). TGF-β1 levels in the conditioned media did not change with donor age. There was a lack of association between TGF-β levels in vitro and the concentration of matrix-associated TGF-β in vivo. TGF-β1 levels failed to be associated with the local trabecular bone volume in the complete study population (r = +0.15, p = 0.16, n = 89). A significant association between TGF-β1 levels and bone volume was present in premenopausal women (r = +0.39, p = 0.02, n = 33), but was largely accounted for by the two samples with the highest TGF-β concentrations. In conclusion, our data suggest that TGF-β1 is the major TGF-β isoform produced by human bone cells in vitro, and that the constitutive secretion of TGF-β by bone cells does not change with age. Whether constitutive differences in TGF-β secretion may be a determinant of human bone mass remains to be clarified in further studies.
Gesehen am 14.05.2021